Self-defeating antitrust laws: How leniency programs solve Bertrand's paradox and enforce collusion in auctions - Giancarlo Spagnolo (Fondazione Eni Enrico Mattei (FEEM), 2000)
I find that current US's and EU's Antitrust laws – in particular their "moderate"' leniency programmes that only reduce or at best cancel sanctions for price-fixing firms that self-report – may make collusion enforceable even in one-shot competitive interactions, like Bertrand oligopolies and first-price auctions, where no collusion would be supportable otherwise. The reduced sanctions for firms that self-report provide the otherwise missing credible threat necessary to discipline collusive agreements: they ensure that if a firm unilaterally deviates from collusive strategies, other firms find it convenient to punish it by reporting information to the Antitrust Authority.
Keywords: D43; D44; K21; L41; 330; Antitrust law; leniency; self-reporting; cartels; collusion; bid-rigging; oligopoly; auctions; Kartellrecht; Kartell; Duopol; Oligopol; Preiswettbewerb; Auktionstheorie; Theorie